Designerly Way of Organizing. The Design of Creative Organization - Francesco Zurlo (Agathón)
In recent years, the Design has expanded its ‘design objects’ to include organization. Specifically, it is within the debate on Design Thinking that this interest emerges, in one of the typologies that characterize it: Creative Confidence. The creative dimension is functional with regard to involving the members of an organization; it allows to overcome the resistance to change and it enables the risk that every creative process entails. The aim is to innovate products and services through greater availability and acceptance, enabled by careful leadership, towards creativity. Design is a creative expression, yet, like creativity itself, it requires the creation and absorption of cultural codes and models; the assumption, in summary, of a ‘design culture’.